The War and Peace of Languages and Cultures. The Teacher and the Student. 21st century Russia. - Ter-Minasova, Svetlana (Armenian Folia Anglistika, 2009)
The article highlights the conflict between teachers and students as one of the most serious educational problems the world and particularly Russia currently faces. Despite the universality of the problem, Russia seems to be suffering from it more than any other country since the conflict is not confined to the generation gap only. Rather, it embodies the conflict between ideologies, cultures and ways of thinking since the Russian teacher and the Russian student have grown up in quite different environments with different values.